Compromised intestinal integrity in older adults during daily activities: a pilot study - Sharon Hendriks (BMC, 2021)
Abstract Background Malnutrition is a common and significant problem in older adults. Insight into factors underlying malnutrition is needed to develop strategies that can improve the nutritional status. Compromised intestinal integrity caused by gut wall hypoperfusion due to atherosclerosis of the mesenteric arteries in the aging gastrointestinal tract may adversely affect nutrient uptake. The presence of compromised intestinal integrity in older adults is not known. The aim of this study is to provide a proof-of-concept that intestinal integrity is compromised in older adults during daily activities. Methods Adults aged ≥75 years living independently without previous gastrointestinal disease or abdominal surgery were asked to complete a standardized walking test and to consume a standardized meal directly afterwards to challenge the mesenteric blood flow. Intestinal fatty acid-binding protein (I-FABP) was measured as a plasma marker of intestinal integrity, in blood samples collected before (baseline) and after the walking test, directly after the meal, and every 15 min thereafter to 75 min postprandially. Results Thirty-four participants (median age 81 years; 56% female) were included. Of the participants, 18% were malnourished (PG-SGA score ≥ 4), and 32% were at risk of malnutrition (PG-SGA score, 2 or 3). An I-FABP increase of ≥50% from baseline was considered a meaningful loss of intestinal integrity and was observed in 12 participants (35%; 8 females; median age 80 years). No significant differences were observed in either baseline characteristics, walking test scores, or calorie/macronutrient intake between the groups with and without a ≥ 50% I-FABP peak. Conclusion This study is first to indicate that intestinal integrity is compromised during daily activities in a considerable part of older adults living independently.